The judicious perceiving of good as its mystical experience - Skrzypek- Faluszczak, Jadwiga (Hybris, 2013)
The Plato’s mysticism arises from a conviction of an existence of two realities. The world of phenomena cannot be recognized by a human, it can only be seen. The whole world of our experience should be put in brackets. The reality which is a subject of our cognition contains an existence inside itself. The speculative thinking is a method of capture an existence by mind. Thus only a philosopher can reach the top of intellectual mysticism. It is a specific experience of mind. Dialectic cognition in its final point is placed beyond speculative cognition. It is a direct seeing of the Good Itself. The communion with It changes the human. Contemplation brings to mind that you are identical with the Final Principle, the Real existence. Judicious perceiving of existence is a natural state of a soul and at the same time an experience of something unique and unusual. The Plato’s mysticism is an inner look at what is the most common and existing. The philosophers are presented as an elite reaching the god’s wisdom, capable of dialectical considering of an existence. Mysticism is an offer for those who are awesome of the world elapsing. Due to this awareness, a human can get his inside and rise to the level of existence in his homeland as well as be granted the true holiness and reach the immortality as gods.